The complex nature of CXCR4 mutations in WHIM syndrome - Rodríguez-Frade, José Miguel; González-Granado, Luis Ignacio; Santiago, César A.; Mellado, Mario (Frontiers in Immunology, 2024)
Heterozygous autosomal dominant mutations in the CXCR4 gene cause WHIM syndrome, a severe combined immunodeficiency disorder. The mutations primarily affect the C-terminal region of the CXCR4 chemokine receptor, specifically several potential phosphorylation sites critical for agonist (CXCL12)-mediated receptor internalization and desensitization. Mutant receptors have a prolonged residence time on the cell surface, leading to hyperactive signaling that is responsible for some of the symptoms of WHIM syndrome. Recent studies have shown that the situation is more complex than originally thought, as mutant WHIM receptors and CXCR4 exhibit different dynamics at the cell membrane, which also influences their respective cellular functions. This review examines the functional mechanisms of CXCR4 and the impact of WHIM mutations in both physiological and pathological conditions.The elucidation of the CXCR4 gene and its impact on human immunology followed several key discoveries in the 1990s and the early 2000s. The CXCR4 gene was first identified and characterized in the 1990s. Initial efforts mapped the gene to chromosome 2q21 using isotopic in situ hybridization (1, 2). The genomic structure of the CXCR4 gene was determined by Wegner et al. in 1998 (3). Key elements in the CXCR4 promoter include a TATA box, a nuclear respiratory factor-1 (NRF-1) site, and two GC boxes, which are critical for the regulation of gene expression.